Effectiveness of Elastomeric Half-Mask Respirators vs N95 Filtering Facepiece Respirators During Simulated Resuscitation: A Nonrandomized Controlled Trial - Barros, Andrew J. (JAMA Netw Open, 2021)
This nonrandomized controlled trial compares the effectiveness of elastomeric half-mask respirators with that of N95 filtering facepiece respirators during cardiopulmonary resuscitation.